Incentives to (Irreversible) Investments Under Different Regulatory Regimes - Carlo Scarpa; Paolo Panteghini (Center for Economic Studies and ifo Institute (CESifo), 2001)
This paper addresses the issue of how regulatory constraints affect firm's investment choices when the firm has the option to delay investment. The RPI-x rule is compared to a profit sharing rule, which increases the x factor in case profits go beyond a given level. It is shown that these rules are identical in their impact on investment choices, in that the change in the option value exactly compensates the change in the direct profitability of investment. The result is then analysed in the light of option theory and explained on the basis of the bad news principle.
Keywords: L51; 330